Sosialisasi Dan Bakti Sosial Pembagian Masker Dan Hand Sanitizer Kepada Masyarakat Sebagai Upaya Mengurangi Angka Penyebaran Covid-19 - Dwi susiloningrum; Susan Primadevi; Dian Arsanti Palupi; Lilis Sugiart; Endra Pujiastuti (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2022)
Background Since 2020, Indonesia has experienced the Covid-19 pandemic, and large-scale social restrictions (PSBB) have begun to be implemented. The number of Covid-19 sufferers in Indonesia has increased from 2020- 2021. One of the efforts to overcome this increase is by providing social services for distributing masks and hand sanitizers to the public. Purpose: Efforts to reduce the number of Covid-19 in society. Method: Distribution of masks and hand sanitizers in the tourist area of the Menara Kudus as well as an explanation of how to use them orally. ResultsThe 100 people who were targeted were already wearing masks and hand sanitizers. Conclusion: People in the tourist area of Menara Kudus, people already wear masks and hand sanitizers when they leave the house